A Novel One‐Step Synthesis of Silicon‐Containing Arylacetylene Resin Catalyzed by Et2Zn with Excellent Processability and Thermal Properties. Issue 11 (16th March 2022) - Chen, Fan; Dong, Sensen; Zhao, Chuanqing; Hu, Wei; Wang, Guihui; Hu, Yanhong; Deng, Shifeng
Abstract: A novel one‐step synthesis of silicon‐containing arylacetylene resin (PSA) catalyzed by Et2 Zn was reported. PSA‐Et2 Zn was prepared by the reaction between diethynylbenzene and dichlorodimethylsilane in the presence of diethylzinc. The structure of PSA‐Et2 Zn was determined and the reaction mechanism was proposed. In addition, the processability, thermal curing behavior, and thermal properties were studied. When compared with the zinc powder catalysis method, the Et2 Zn catalysis method demonstrates a greater effectiveness in avoiding the formation of olefinic products at the ends of the molecular chain, which can improve thermal capabilities. The results show that PSA‐Et2 Zn possesses excellent processability and thermal properties. PSA‐Et2 Zn has a wide processing window of 35∼182 °C and the thermal crosslinking reactions of PSA‐Et2 Zn resin are mild. The cured PSA‐Et2 Zn shows high thermal stability with a residue yield up to 87.9 % at 800 °C. Furthermore, the temperature at 5 % weight loss in nitrogen and air atmospheres is 584 °C and 539 °C, respectively. Abstract : Silicon‐containing arylacetylene resin (PSA) has several possible applications in semiconductor materials, aerospace and high‐frequency communications. Growing scholarly and industry attention has been devoted to the potential application of PSA in recent years. In this paper, a novel one‐step synthesis of PSA catalyzed by Et2 Zn was reported, which provides an uncomplicated and effective way to prepare PSA with excellent processability and thermal properties.